THE USE OF INTERNET MEDIA AND ITS CORRELATION WITH THE SPIRITUAL DEVELOPMENT OF 11TH-GRADE STUDENTS AT IMMANUEL PRIVATE CHRISTIAN SENIOR HIGH SCHOOL, MEDAN, IN THE YEAR 2023 - Saragih, Novita Romauli; Karo-Karo, Selamat; Zega, Eka Prasetia; Wiharjokusumo, Padriadi (JURNAL DARMA AGUNG, 2024)
This study examines the correlation between the use of internet media and the spiritual development of 11th-grade students at Immanuel Private Christian Senior High School, Medan, in 2023. The study uses a descriptive-correlational research design and encompasses the entire population of 30 students. Data are collected using a questionnaire and a spiritual development scale, and analyzed using descriptive and inferential statistics. Results show that the students use internet media frequently and mostly for social and entertainment purposes, and have a moderate level of spiritual development. Results also show that there is a significant negative correlation between the use of internet media and the spiritual development of the students, as well as for some of its dimensions. The study discusses the implications and limitations of the results, and suggests directions for further research.